2019
DOI: 10.1108/md-11-2016-0784
|View full text |Cite
|
Sign up to set email alerts
|

Internal factors & consequences of business model innovation

Abstract: Purpose The purpose of this paper is to propose a theoretical model of business model innovation based on evidences from the past literature. The paper established a link between business model innovation (BMI) strategic flexibility, competitive advantage and firm competence. Design/methodology/approach The study was approached from a theoretical perspective using previous literature on BMI from 2000 to 2017, as per the recommendations of Tranfield et al. (2003). A total of 104 conceptual and empirical artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 106 publications
1
69
1
2
Order By: Relevance
“…The results revealed that service innovation success carries the positive mediation effect among the innovation capabilities and the innovation in business model. This finding is also found to in line with the existing literature that proposed and identified the theoretical logic for the possible relationship (Bashir & Verma, 2019).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results revealed that service innovation success carries the positive mediation effect among the innovation capabilities and the innovation in business model. This finding is also found to in line with the existing literature that proposed and identified the theoretical logic for the possible relationship (Bashir & Verma, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, it may not be wrong to state that the overall strength of innovation capabilities of an organization lies at the extent of the value it captures for itself and delivers for customer. This fact is also indicated by many other researchers that debated that innovation capabilities are truly reflected in the extent of value capture and value deliver by the organization (Bashir & Verma, 2019). This also indicates the persuasion of continuous innovation by the organization in development of new business model(s).…”
Section: Hypotheses Developmentmentioning
confidence: 62%
See 1 more Smart Citation
“…Business model innovation can help to create competitive advantage not only locally, but also internationally. Autio (2017) examined business model innovation of international new ventures. He states that there are a few conditions that need to be met in order for INV to stay competitive in the international environment.…”
Section: Resultsmentioning
confidence: 99%
“…Adapting the business model is a risky venture as there is no way of knowing whether one will succeed. Central themes in the field of strategy pertain to sustaining competitive advantage and creating value in firms and industries (Bashir & Verma, 2019). The business model has become an essential tool in achieving these factors.…”
mentioning
confidence: 99%